2008
DOI: 10.1002/jcu.20486
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic appearances of the normal ulnar nerve in the cubital tunnel

Abstract: There were differences in the CSA of the ulnar nerve between some age groups, but there was no variation with sex or handedness. Sonography can evaluate the morphologic changes of the nerve during flexion of the elbow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
60
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 20 publications
6
60
1
Order By: Relevance
“…However, the relatively higher frequency of perching relative to dislocation is consistent with prior reports in the literature 2,4,5,14 . We suspect that our investigational methods may have contributed to our findings.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…However, the relatively higher frequency of perching relative to dislocation is consistent with prior reports in the literature 2,4,5,14 . We suspect that our investigational methods may have contributed to our findings.…”
supporting
confidence: 91%
“…The nerves that dislocate on physical examination are treated primarily with ulnar nerve transposition or epicondylectomy. If we had excluded perchable nerves from our subject group, the overall prevalence of hypermobility was 26% and the data would more closely correlate with those of Ozturk et al, who documented subluxation in 23% and dislocation in 8.5% of 212 elbows 14 . The high degree of bilateral hypermobility that was noted supports a similar finding by Ashenhurst 5 .…”
supporting
confidence: 62%
“…There are 3 earlier dynamic ultrasound studies about (sub)luxation during elbow flexion in healthy controls. 5,8,9 One study showed subluxation in 53 of 200 elbows (27%) and luxation in 39 elbows (20%). 8 Another study of 212 elbows found subluxation in 49 (23.1%) and luxation in 18 elbows (8.5%).…”
Section: Discussionmentioning
confidence: 97%
“…8 Another study of 212 elbows found subluxation in 49 (23.1%) and luxation in 18 elbows (8.5%). 9 The third study revealed ulnar nerve displacement in 24.3% of 78 elbows from 39 healthy subjects; 20.5% (16/78) had subluxation, and 3.8% (3/78) had luxation. 5 These earlier reported incidences in healthy subjects are much higher than in our study (5.7% for both luxation and subluxation).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation